SIFAT BIOLOGI TANAH MINERAL MASAM DYSTRUDEPTS DI AREAL PIRINGAN KELAPA SAWIT YANG DIAPLIKASI MULSA ORGANIK Mucuna Bracteata DI LAHAN PERCOBAAN FAKULTAS PERTANIAN, UNIVERSITAS RIAU - Zahara, Fitri; ', wawan; ', Wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objectives of this research to determine the soil biological properties on the acidic mineral soil Dystrudepts in the area of disc palm oil applied of organic mulch Mucuna bracteata in the experimental garden of Agriculture Faculty, Riau University. Analysis of the soil biological was conducted in the Soil Laboratory of Agriculture Faculty, Riau University, in October 2014 to February 2015. Application of mulch organic M. bracteata used purposive random sampling method which consisting of 4 levels and 4 replications. The levels is M0 (0 kg /plant), M1 (15 kg /plant), M2 (30 kg /plant) and M3 (45 kg /plant). Parameter observed : calculate the amount of soil biota macrofauna, mesofauna and microorganism. Data were analyzed deskriptively statistically. The research showed application of organic mulch M. bracteata 45 kg/plant increased the amount of soil biota macrofauna, mesofauna and microorganism soil, in the area of disc palm oil. Keywords: Soil biological properties, Dystrudepts, Mucuna bracteata